Hubungan Persepsi Ibu, Dukungan Suami, dan Dukungan Tenaga Kesehatan terhadap Pemberian Asi Ekslusif pada Ibu Menyusui di Wilayah Kerja Puskesmas Cahya Maju Lempuing Oki Tahun 2021 - Ema Yuliana; Murdiningsih Murdiningsih; Putu Lusita Nati Indriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Exclusive breastfeeding is breast milk that is given to babies from birth for 6 months, without adding and or replacing with other food or drinks. WHO reports globally that the average rate of exclusive breastfeeding in the world in 2017 is only 38%. The purpose of the study was to determine the relationship between mother's perception, husband's support, and support from health workers on exclusive breastfeeding in the Cahya Maju Lememburu PublicHealth Center Work Area OKI. Data from the Cahya Maju Lemrubuk Public Health Center OKI in 2018, from 157 mothers who had babies 0-6 months, 85.35% (134 mothers) gave exclusive breastfeeding and 14.65% (23 people). In 2019, out of 235 mothers, only 49.79% (117 mothers) gave exclusive breastfeeding and 50.21% (118 mothers). In the initial study at the Cahya Maju Public Health Center, Lemrubuk OKI, data was obtained from 240 mothers who had babies 0-6 months, only 17.5% (42 mothers) exclusively breastfed and 82.5% (198 mothers). The population in this study were 240 mothers who had babies aged 6 months. The sampling technique used simple random sampling with 71 mothers. Analysis using chi-square test. The results show that there is a relationship between mother's perception and P-value = 0.003, husband's support P-value = 0.004, health worker support P-value = 0.000. It can be concluded that there is a relationship between mother's perception, husband's support and support from health workers with exclusive breastfeeding for breastfeeding mothers in the Cahya Maju Lemembur Public Health Center Work Area OKI 2021. The results of this study are expected to be input for providing input to improve health worker services to the community, especially in providing information about exclusive breastfeeding.